Academic training increases grounding of scientific concepts in experiential brain systems. (14th December 2022) - Ulrich, Martin; Harpaintner, Marcel; Trumpp, Natalie M; Berger, Alexander; Kiefer, Markus
Abstract: Scientific concepts typically transcendent our sensory experiences. Traditional approaches to science education therefore assume a shift towards amodal or verbal knowledge representations during academic training. Grounded cognition approaches, in contrast, predict a maintenance of grounding of the concepts in experiential brain networks or even an increase. To test these competing approaches, the present study investigated the semantic content of scientific psychological concepts and identified the corresponding neural circuits using functional magnetic resonance imaging (fMRI) in undergraduate psychology students (beginners) and in graduated psychologists (advanced learners). During fMRI scanning, participants were presented with words denoting scientific psychological concepts within a lexical decision task (e.g. "conditioning", "habituation"). The individual semantic property content of each concept was related to brain activity during abstract concept processing. In both beginners and advanced learners, visual and motor properties activated brain regions also involved in perception and action, while mental state properties increased activity in brain regions also recruited by emotional–social scene observation. Only in advanced learners, social constellation properties elicited brain activity overlapping with emotional–social scene observation. In line with grounded cognition approaches, the present results highlight the importance of experiential information for constituting the meaning of abstract scientific concepts during the course of academic training.